De fyra stegen till stolthet : En kvalitativ studie om hur Boden och Mariestad, genom upplevelseproduktion, kan uppnå stoltare invånare - Nordström, Julia; Landström, Hanna (2011)
Today there is great competition between municipality, regions and countries when it comes to people’s awareness and choice of hometown and holiday-destinations. For a destination to appeal to a potential visitor it is important that it has a good image. If those who live at the destination, that is to say those with the best knowledge of the destination, doesn’t feel at home there or if they speak badly about the destination it affects the image badly. If those who has the best knowledge of the destination doesn’t feel at home there or talks badly about it, who will then want to visit it? With that groundwork we wanted to know how the inhabitant’s in our home-municipality, Boden and Mariestad, see their hometown, what picture are they painting for others and how do the destinations can work to improve this? The purpose with this essay is to develop strategies for Boden and Mariestad using experience production management to gain prouder inhabitants, which in turn talk positively about their hometown with outsiders. We made qualitative interviews with private persons in Boden and Mariestad to find out how they experience their hometown. Practitioners on both destinations were also interviewed to see if they actively work to achieve prouder inhabitants. To contribute with successful solutions to our strategies we studied a successful destination in the area, Piteå. In Boden they have noticed the problem with a negative image and are now actively working with a pride campaign that are divided in several different projects. Mariestad on the other hand doesn’t work very active to gain prouder inhabitants. That is why the strategy for Mariestad shows that inhabitants in Mariestad need to learn to brag more about Mariestad. This because they’re going to be prouder of living in Mariestad. We feel that both destinations need to work further with improving the image that their inhabitants are spreading. Validerat; 20110703 (anonymous)